2021
DOI: 10.3390/medicina57020110
|View full text |Cite
|
Sign up to set email alerts
|

Review of Medical Therapies for the Management of Pulmonary Embolism

Abstract: Traditionally, the management of patients with pulmonary embolism has been accomplished with anticoagulant treatment with parenteral heparins and oral vitamin K antagonists. Although the administration of heparins and oral vitamin K antagonists still plays a role in pulmonary embolism management, the use of these therapies are limited due to other options now available. This is due to their toxicity profile, clearance limitations, and many interactions with other medications and nutrients. The emergence of dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 120 publications
0
7
0
Order By: Relevance
“…Second, for the thrombotic patients without an obvious trigger or with an irremovable trigger, anticoagulation is a must. For instance, although balloon pulmonary angioplasty (BPA) is an effective interventional modality for the patients with CTEPH, especially for the CTEPH patients with thrombi in the distal pulmonary arteries, the oral anticoagulant drugs such as warfarin, should be maintained lifetime to prevent recurrence of CTEPH following BPA ( Panahi et al, 2021 ).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Second, for the thrombotic patients without an obvious trigger or with an irremovable trigger, anticoagulation is a must. For instance, although balloon pulmonary angioplasty (BPA) is an effective interventional modality for the patients with CTEPH, especially for the CTEPH patients with thrombi in the distal pulmonary arteries, the oral anticoagulant drugs such as warfarin, should be maintained lifetime to prevent recurrence of CTEPH following BPA ( Panahi et al, 2021 ).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…A therapeutic dose of anticoagulants should be used timely if there is no anticoagulant contraindication ( Table 2 ). 72 , 73 , 74 , 75 , 76 , 77 Systematic thrombolytic therapy, such as, recombinant tissue type plasminogen activator (r-tPA), 50 mg intravenous infusion for 2 h, is recommended only for patients at a high risk of PTE. 70 For trauma patients with contraindications to systemic thrombolysis, pulmonary interventional thrombolysis, or thrombus aspiration can be considered, even under the condition that extracorporeal membrane oxygenation was needed for help.…”
Section: Treatment and Prevention Of Trauma Vtementioning
confidence: 99%
“…Both low dose unfractionated heparin (5000U Q12H) and LMWH (30 mg Q12H) enoxaparin administered after trauma can effectively prevent the occurrence of VTE and be safely adjusted based on the anti-Xa levels. 72 , 103 Weight-based and blood for the anti-Xa testing should be typically drawn 4 h after the third dose of enoxaparin, that with the target prophylactic levels falling in the range of 0.2–0.4 IU/mL (the target for therapeutic full anticoagulation is > 0.5 IU/mL) is recommended. But one larger retrospective study 104 reported no decrease in VTE rates with an anti-Xa-based regimen.…”
Section: Treatment and Prevention Of Trauma Vtementioning
confidence: 99%
“…The oral bioavailability is approximately 50%, with most of the drug absorption occurring in the small intestine [115]. Drug elimination occurring via the metabolism through the CYP3A4 systems in the intestine and liver and the P-glycoprotein system can be enhanced through drug-drug interactions Apixaban [116].…”
Section: Apixabanmentioning
confidence: 99%